1993
DOI: 10.1111/j.1476-5381.1993.tb13456.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the endothelium and hypoxia on α1‐ and α2‐adrenoceptor‐mediated responses in the rabbit isolated pulmonary artery

Abstract: 1 The effects of the inhibitor of nitric oxide synthase, N'0-nitro-L-arginine methylester (L-NAME, i0' M), mechanical disruption of the endothelium and hypoxia on contraction to noradrenaline (al-and x2-adrenoceptor agonist), phenylephrine (a,-adrenoceptor agonist) and UK 14304 (@2-adrenoceptor agonist) were compared in the rabbit isolated pulmonary artery. The effects of the selective antagonists rauwolscine (10-6 M, M2-adrenoceptors) and prazosin (10-' M, ax-adrenoceptors) on the contractions to noradrenalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
5

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
(24 reference statements)
4
21
0
5
Order By: Relevance
“…The underlying mechanism for this phenomenon has still to be determined. We have previously shown that inhibition of nitric oxide synthase also potentiates responses to noradrenaline and the M2-adrenoceptor agonist UK 14304, in both rabbit isolated pulmonary arteries and the rat isolated perfused lung (Shaw et al, 1992;MacLean et al, 1993). The combined effect of the increased sensitivity to nerve stimulation, shown in the present study, and to circulating catecholamines would be likely to aggravate further pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The underlying mechanism for this phenomenon has still to be determined. We have previously shown that inhibition of nitric oxide synthase also potentiates responses to noradrenaline and the M2-adrenoceptor agonist UK 14304, in both rabbit isolated pulmonary arteries and the rat isolated perfused lung (Shaw et al, 1992;MacLean et al, 1993). The combined effect of the increased sensitivity to nerve stimulation, shown in the present study, and to circulating catecholamines would be likely to aggravate further pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 55%
“…We have shown that transient inhibition of nitric oxide is responsible for the transient vasoconstrictor response to acute hypoxia in rabbit pulmonary arteries (MacLean & McGrath, 1991). Inhibition of nitric oxide synthase with N0-nitro-L-arginine methylester (L-NAME) potentiates post-junctional response to noradrenaline in rabbit pulmonary arteries and the rat perfused lung and in the former, this effect appears to involve X2-adrenoceptor stimulation (Shaw et al, 1992;MacLean et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…We reported that norepinephrine infusion induces a potent NO-dependent pulmonary vasodilation in fetal lambs (17). As ␣ 2 -adrenoceptor antagonists were found to inhibit norepinephrine-mediated relaxation of pulmonary (16,18) or systemic arteries (15), or enhance norepinephrine-mediated pulmonary vasoconstrictive response (8,9), norepinephrine-mediated pulmonary vasodilation may result from activation of endothelial ␣ 2 -adrenoceptors.…”
mentioning
confidence: 98%
“…The vasodilator action of several substances, such as acetylcholine, bradykinin, or ADP, and shear stress are dependent, at least in part, on NO release (6). More recently, in vitro studies reported that NO release and pulmonary vasorelaxation can also be mediated by endothelial ␣ 2 -adrenoceptor activation (7)(8)(9). However, little is known about the role of ␣ 2 -adrenoceptors on the basal pulmonary vascular tone during fetal life and on the adaptation of the pulmonary circulation at birth.…”
mentioning
confidence: 99%
“…This could have functional signi®cance, as sympathetic stimulation causes changes in pulmonary vascular resistance that are mediated via noradrenaline and a-and b-adrenoceptors (Hyman et al, 1990). We have previously shown that relaxation of PGF 2a constricted rat pulmonary arteries by b-adrenoceptor agonists is largely endothelium dependent and mediated via nitric oxide (NO) (Priest et al, 1997), and there is evidence that noradrenaline-induced vasoconstriction of pulmonary arteries may be depressed due to stimulation of NO synthesis via both a-and b-adrenoceptors (MacLean et al, 1993;Tulloh et al, 1994;Priest et al, 1997). Constriction of porcine pulmonary arteries with the a 1 -adrenoceptor agonist phenylephrine (PE) has also been associated with an endothelium-dependent rise in cyclic GMP (Pepke-Zaba et al, 1993).…”
Section: Introductionmentioning
confidence: 99%